Strengthening Communities through Grassroots Democracy Development in Thailand - Singkaneti, Banjerd (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Facilitating collaborative group activities between the civil society network and relevant academic networks to carry out the task of developing area development plans and bolstering member participation in building a robust and sustainable community, which contributes to the growth of Thai democracy Thus, research into creating robust communities and the advancement of democracy in Thailand. Thus, this paper examines the critical endeavor of bolstering communities and nurturing grassroots democracy in Thailand. Through a thorough investigation, it delves into four key aspects: elucidating the conceptual underpinnings of democracy at the local level, identifying the essential sociological conditions necessary for fostering grassroots democracy in Thailand, proposing guidelines for integrating democratic principles within local communities and presenting a summary of operational strategies deployed during the initial phase of the research. Methodology: This research was conducted as a qualitative study by extracting lessons learned from the action research project. “Social innovation to build strong communities based on “Thai Identity Democracy” by studying academic documents and field studies Data were analyzed using the Thematic analysis method. Result: Emphasizing the necessity of implementing robust measures and mechanisms to drive community development, the study particularly underscores the central role of coordination at the provincial level and the establishment of a "Public Sphere". Additionally, it advocates for collaborative partnerships with network organizations within the public sector to collectively advance the community empowerment agenda. Strengthened and united communities are portrayed as pivotal agents in local governance, equipped to tackle pressing issues affecting their members. By cultivating active community engagement in problem-solving endeavors, the groundwork is laid for addressing structural inequalities and nurturing a distinctively Thai democratic ethos grounded in communal cooperation. Conclusion: Overall, the data emphasizes how important it is to take strong action and work together to promote community development, focusing on public sector partnerships and provincial coordination. It prepares the way for tackling inequality and establishing a distinctly Thai democratic ethos based on group collaboration by empowering communities and encouraging active participation.